Gait Progression Over 6 Years in Parkinson’s Disease: Effects of Age, Medication, and Pathology - Wilson, Joanna; Alcock, Lisa; Yarnall, Alison J.; Lord, Sue; Lawson, Rachael A.; Morris, Rosie; Taylor, John-Paul; Burn, David J.; Rochester, Lynn; Galna, Brook (Frontiers in Aging Neuroscience, 2020)
Background: Gait disturbance is an early, cardinal feature of Parkinson's disease associated with falls and reduced physical activity. Progression of gait impairment in Parkinson’s disease is not well characterised and a better understanding is imperative to mitigate impairment. Subtle gait impairments progress in early disease despite optimal dopaminergic medication. Evaluating gait disturbances over longer periods, accounting for typical aging and dopaminergic medication changes, will enable better understanding of gait changes and inform targeted therapies for early disease. The aim of this study was to describe gait progression over the first six years of Parkinson’s disease by delineating changes associated with aging, medication and pathology. Methods: 109 newly diagnosed Parkinson’s disease participants and 130 controls completed at least two gait assessments. Gait was assessed at 18-month intervals for up to six years using an instrumented walkway to measure sixteen spatiotemporal gait characteristics. Linear mixed-effects models assessed progression. Results: Ten gait characteristics significantly progressed in Parkinson’s disease, with changes in four of these characteristics attributable to disease progression. Age-related changes also contributed to gait progression; changes in another two characteristics reflected both aging and disease progression. Gait impairment progressed irrespective of dopaminergic medication change for all characteristics except step width variability. Conclusions: Discrete gait impairments continue to progress in Parkinson’s disease over six years, reflecting a combination of, and potential interaction between, disease-specific progression and age-related change. Gait changes were mostly unrelated to dopaminergic medication adjustments, highlighting limitations of current dopaminergic therapy and the need to improve interventions targeting gait decline.